NATIONAL LEGAL DEVELOPMENT POLICY AND THE ROLE OF AUTHORITIES IN LEGAL DEVELOPMENT (A STUDY ON LEGAL DEVELOPMENT THAT CONFIRMS THAT LAW MUST BE USED FOR DEVELOPMENT INTERESTS) - Al Faraby, Ahmad Habib; Muhammad, Mukmin; Yamin, Ahmad Fachri (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal